Eco-Friendly information literacy in green and sustainable business programs - Maulina, Ajri Rhaysa; Kurniasih, Nuning; Saepudin, Encang (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Eco-friendly information literacy plays an important role in helping to change public behavior towards a more environmentally friendly lifestyle. Purpose: The aim of this research is to examine various aspects of information literacy within the green and sustainable business programs conducted by The Local Enablers (TLE) in an eco-friendly context. Method: The research method employed is qualitative descriptive study. The research subject is based on the involvement of specific parties with the research object to be studied in-depth. The subjects involved in this study consist of several individuals who play roles in the TLE project team during the planning and implementation of green and sustainable business programs. Findings: This research outlines the information literacy process in the green and sustainable business program at TLE according to the Big6 Model theory, from problem formulation to information evaluation. The Big6 Model assists TLE as a problem-solving framework for the information needs of the green and sustainable business program. Each member of the TLE team is able to explain the process of searching for and using information during program development. Conclusion: Eco-friendly information literacy is well-established within TLE, where they actively seek out and implement new environmental information within the TLE ecosystem. In designing and implementing green and sustainable business programs, TLE recognizes the urgency of environmental issues and understands that the process of information literacy is an effective problem-solving tool.